Bio-based polyurethane nanocomposite thin coatings from two comparable POSS with eight same vertex groups for controlled release urea - Lixia Li (Nature Portfolio, 2021)
Abstract Nanocomposite modification has attracted much attention in improving properties of bio-based polymer coating material for coated fertilizer. Herein two comparable polyhedral oligomeric silsesquioxanes (POSS), with eight poly(ethylene glycol) (PEG) and octaphenyl groups attached to the cage, respectively, were successfully incorporated into thin castor oil-based polyurethane coatings via in-situ polymerization on the urea surface. The nanostructure coatings are environmentally friendly, easy to prepare, and property-tunable. The results show that the vertex group of POSS had a pronounced influence on dispersion level and interaction between polyurethane and POSS that well-tuned the release pattern and period of coated urea, even at the coating rate as low as of 2 wt%. The liquid POSS with long and flexible PEG groups had better compatibility and dispersibility in polyurethane matrix than the solid POSS with rigid octaphenyl groups, as evidenced by SEM/EDS. The unique properties were resulted from the different extents of physical crosslinkings. This modification of bio-based polyurethane coating with POSS provided an alternative method of regulating and controlling the properties of coated fertilizer.